Legal Issues and Solutions for AI Face-swapping Technology in the Context of the rule of the Law - Yin, Wenyi (Journal of Theory and Practice of Social Science, 2024)
In the context of the rule of law in the new era of network, the protection of personal information rights and interests is an important content of great concern. Through empirical research on the use of AI face-swapping technology, the legal issues in AI face-swapping can be categorized from civil infringement and criminal offense respectively. On this basis, the five aspects of regulating network technology, regulating network platforms, clarifying the main responsibility, improving Blockchain technology, and enhancing citizens' network rule of law literacy can be taken as the "entry point" to regulate the use of AI face-swapping technology, so as to safeguard network security and create a clear cyberspace environment.